Science Misconceptions on Earth Layer Concepts among Junior High Students: Kesalahpahaman Ilmiah tentang Konsep Lapisan Bumi di Kalangan Siswa SMP - Wijaya , M. Rizal Setia; Shofiyah, Noly (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Education consistently requires students not only to master content but also to comprehend interrelated concepts, making misconceptions common in science learning. Specific background: In junior high schools, especially in the context of natural science learning, complex topics such as Earth layers often generate misunderstandings that affect further conceptual development. Knowledge gap: While misconceptions in science have been widely recognized, limited empirical studies explore how these misconceptions manifest in Muhammadiyah school settings. Aims: This study investigates the types and prevalence of misconceptions among Grade VII students at SMP Muhammadiyah 9 related to Earth layer material. Results: Using a survey approach with the Three-Tier Multiple Choice Diagnostic Test, findings revealed misconceptions across all subchapters. Male students showed the highest misconception rate (65.9%) in identifying elements of the atmosphere, while female students reached the highest rate (74.2%) in understanding temperature in the mesosphere and the ozone layer. Novelty: This study provides specific evidence of gender-based misconception patterns within a Muhammadiyah boarding school, offering new insights into science education challenges in faith-based institutions. Implications: Results underscore the need for diagnostic-based instructional interventions to address misconceptions and improve conceptual accuracy in science education.Highlights: Misconceptions persist across all Earth layer subchapters. Gender patterns show different misconception dominance. Findings suggest targeted interventions for science learning. Keywords: Misconceptions, Junior High School, Science Education, Earth Layer, Diagnostic Test